1972
DOI: 10.1111/j.0954-6820.1972.tb05328.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Metabolic Effects of Ethanol by Fructose

Abstract: Abstract. Present knowledge of the metabolic interactions between fructose and ethanol in man and laboratory animals is reviewed. The possible biochemical mechanisms of these interactions are considered. Some new data on the effects of fructose and ethanol on carbohydrate and lipid metabolism are included. Fructose increases the effects of ethanol on the hepatic lactate/pyruvate and a‐glycerophosphate/dihydroxyacetone phosphate ratios. Thus it augments the basic metabolic effect of ethanol, i.e. reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

1976
1976
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 50 publications
2
2
1
Order By: Relevance
“…depending on the group assignment, the animals either received a single dose of alcohol (5 g/kg, 30% ethanol, EtOH) or control solution (sodium chloride, Nacl 0.9%, ctrl) via oral gavage either 2 h (acute) or 12 h (sub-acute) before experimentation. Previous studies using the same dose of EtOH clearly demonstrated alcohol-dependent changes in the liver, including decreased graft survival, disturbance of hepatic microcirculation and increased triglyceride content (19)(20)(21). This is consistent with our previous studies, in which fatty liver was induced by this dose and concentration of alcohol (2,22).…”
Section: Methodssupporting
confidence: 92%
“…depending on the group assignment, the animals either received a single dose of alcohol (5 g/kg, 30% ethanol, EtOH) or control solution (sodium chloride, Nacl 0.9%, ctrl) via oral gavage either 2 h (acute) or 12 h (sub-acute) before experimentation. Previous studies using the same dose of EtOH clearly demonstrated alcohol-dependent changes in the liver, including decreased graft survival, disturbance of hepatic microcirculation and increased triglyceride content (19)(20)(21). This is consistent with our previous studies, in which fatty liver was induced by this dose and concentration of alcohol (2,22).…”
Section: Methodssupporting
confidence: 92%
“…Several studies indicate that ethanol and carbohydrates modify the metabolisms of each other ( OGATA et al 1966;FORSANDER et al 1958;YLIKAHRI et al 1972). We found no clear hypoglycaemia, as KELLY et al (1970) did, even though hypoglycaemia has usually been observed during hangover ( VARTIA et al 1960;OGATA et al 1966;YLIKAHRI et al 1974).…”
Section: Effect Of Sugars On Hangoversupporting
confidence: 63%
“…We found no clear hypoglycaemia, as KELLY et al (1970) did, even though hypoglycaemia has usually been observed during hangover ( VARTIA et al 1960;OGATA et al 1966;YLIKAHRI et al 1974). We were also unable to find any decreased blood ethanol level in subjects receiving sugars, even though glucose and fructose have been found to accelerate the ethanol elimination rate ( DAMGAARD et al 1972;THIEDEN et al 1972;YLIKAHRI et al 1972). The administration of monosaccharides had subjectively no effect on hangover.…”
Section: Effect Of Sugars On Hangovercontrasting
confidence: 40%
See 1 more Smart Citation
“…In the present study, we evaluated the effect of a binge‐like ethanol treatment, 12 h before the onset of H/R. Previous studies using doses of 5 g·kg −1 of ethanol clearly demonstrated ethanol‐dependent changes in the liver, that is, decreased graft survival and disturbance of hepatic microcirculation as well as increased triglyceride content (Ylikahri et al ., 1972; Zhong et al ., 1996; Enomoto et al ., 2000) This is consistent with our study where a fatty liver was induced by this dose of ethanol (Figure 1). Taken together, these data provide a valid basis for using ethanol at a dose of 5 g·kg −1 to study the effects of an acute fatty liver in inflammatory conditions, that is, with the H/R procedure.…”
Section: Discussionmentioning
confidence: 99%